Expression of No Affinity Tagged Recombinant Human Interferon Alpha-2a in Methilotropic Yeast Pichia pastoris - Herawati, Neng; Wardiana, Andri; Ningrum, Ratih Asmana (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2015)
Recombinant human interferon alpha-2a (rhIFNÎ±-2a) has been widely used for clinical therapy as antiviral, anticancer as well as immunomodulator. In this study, the open reading frame (ORF) encoding synthetic hIFNÎ±-2a was constructed to be in framed with N-terminal alpha factor secretion system in methylotropic yeast Pichia pastoris. This research aimed to construct, express and analyse the non-affinity tagged recombinant human interferon alpha-2a in the methilotropic yeast P. pastoris. We used pPICZÎ±B plasmid for cloning and expression vector. The confirmed recombinant plasmid containing the correct DNA sequence of hIFNÎ±-2a was linearized by SacI restriction enzyme, then transformed into P. pastoris genome using electroporation. We screened two multi-copy recombinants in YPDS plates containing Zeocinâ¢. Buffered complex medium containing 0.5 % methanol (BMMY) was used for protein expression for 48 hours in the culture condition. The recombinant protein was purified by blue sepharose affinity chromatography. Analyses of hIFNÎ±-2a protein by SDS-PAGE and Western blot confirmed that protein band in which was observed around 19.2 kDa, was recombinant hIFNÎ±-2a. The quantification of purified rhIFNÎ±-2a using colorimetric binichoninic assay (BCA) informed that the yield was 44 mg/L culture (OD600= 2-3).